Surface roughness of monolithic zirconia ceramic submitted to different polishing systems - Deise Caren Somacal; Júlia Willers Dreyer; Patrícia Danesi; Ana Maria Spohr (Universidade Estadual de Campinas, 2019)
Aim: The objective was to evaluate, quantitative and qualitative, the abrasive effect of three polishing systems on the monolithic zirconia ceramic. Methods: Thirty disk-shaped samples of Yttria Tetragonal Zirconia Polycrystal (Y-TZP) were randomly distributed in three groups (n = 10) according to polishing system: G1- Komet system (KO); G2 - CeraGloss system (CG); G3 - Eve Diacera system (EV). The surface roughness (Ra) was obtained with Rugosimeter in four different moments: a) initial - glaze sample (Ra0); b) after occlusal adjustment with diamond burs (Ra1); c) after polishing with the abrasive systems (Ra2); d) after polishing with felt disc and diamond paste (Ra3). Four additional samples were observed in scanning electron microscopy (SEM). Results: According to the Generalized Estimating Equation followed by the Bonferroni test (α = 0.05), the CG provided the lowest Ra2 (0.63 μm), not differing significantly from the KO (0.78 μm). The highest Ra2 was obtained with the EV (0.97 μm), which did not differ significantly from the KO. There was no statistical difference in Ra between the polishing with the abrasive systems (Ra2) and the final polishing with diamond paste (Ra3). SEM images showed that the polishing systems did not completely remove the grooves caused by the diamond burs during the occlusal adjustment. Conclusion: It was concluded that CG promoted smoother surface of the monolithic zirconia ceramic compared to EV, and intermediate smoothness was obtained with KO.